O papel da conectividade e da flora local na composição do banco de diásporos de ambientes aquáticos da planície de inundação do alto rio Paraná. - Ferreira, Fernando Alves (2011)
The floodplain in the upper Parana River can be characterized as a complex landscape influenced by different water systems which interconnect and interact resulting large changes in aquatic macrophyte assemblages. Attributes functional these assemblage are influenced by unidirectional lateral fluxes, as well as dispersion from diaspores by aquatic birds. Diaspores bank in the sediment can actuate as a mechanism for maintenance of the diversity and richness of macrophytes found in this environment. Richness, composition and density of the diaspores bank are the main topics discussed over the tree chapters. First diaspores bank was utilized to test the difference with composition of the macrophyte flora for long periods of floristic inventory. The analyses showed a very distinct composition from diaspores bank and vegetation adult. Posteriorly, compared the richness and density of diaspores bank from distinct water systems to confirm general patterns found along several years for macrophyte assemblage from the floodplain in the upper Paraná River. Finally, evaluated the combination of sampling techniques of the diaspores bank with phytosociological aspects. The results obtained from the diaspores bank confirmed the general patterns and revealed new perspectives on biological knowledge to aggregate to the context of general patterns in macro-scale. These dates supported the understanding of processes of succession in wetlands and showed that the diaspores bank in floodplain provides information valuable mechanisms for restoration of aquatic vegetation for natural disturbance. These studies are pioneer on ecosystems of South America and may contribute to value the environmental services of wetlands on this continent.